INTERAKSI SOSIAL DALAM PELAKSANAAN RITUAL KEAGAMAAN MASYARAKAT HINDU-BALI (Studi Pada Ritual Ngaben di Krematorium) - Suadityawan, I Putu; Kebayantini, Ni Luh Nyoman; Suka Arjawa, I Gusti Putu Bagus (JURNAL ILMIAH SOSIOLOGI (SOROT), 2015)
ABSTRACT Â Ngaben is a religious ceremony conducted by Hindu-Balinese society and has shifted. The shift indicates a change in the interrelation between people in the ceremony ngaben in crematorium. Research question divided into two questions: 1) What factors encourage people choose held ceremony ngaben in crematorium and 2) How the social interaction between people in conducting ceremony ngaben in crematorium. The theory used in this research is the social exchange theory George Caspar Homans. The social exchange theory find an exchange that happened between people who are involved in the ceremony ngaben in crematorium. The people involved in the ceremony ngaben in crematorium have the motivation to benefits earned and affect the social interactions. The research method used was qualitative. Research sites in the Secretariat Maha Gotra Pasek Sanak Sapta Rsi and Crematorium Santha Yana. The result of research shows the factors that encourage people choose held ceremony ngaben in Crematorium Santha Yana is a socio-cultural, social structure, economy, and energy and time. Social interaction in the ceremony ngaben in Crematorium Santha Yana is cooperation and conflict. The conclusion of this research is people choose ceremony ngaben in Crematorium because effective and efficient. Keywords: ngaben in crematorium, social interaction